Serum Laminin γ2 Monomer as a Diagnostic and Predictive Biomarker for Hepatocellular Carcinoma. Issue 2 (28th April 2021) - Yamashita, Taro; Koshikawa, Naohiko; Shimakami, Tetsuro; Terashima, Takeshi; Nakagawa, Masatoshi; Nio, Kouki; Horii, Rika; Iida, Noriho; Kawaguchi, Kazunori; Arai, Kuniaki; Sakai, Yoshio; Yamashita, Tatsuya; et al.
Abstract : Backgrounds and Aims: Structural dynamics of basement membrane components are still to be elucidated in the process of hepatocarcinogenesis. We evaluated the characteristics of HCC expressing laminin γ2 monomer (LG2m), a basement membrane component not detected in normal tissues, for HCC diagnosis. We further determined whether elevated serum LG2m is a risk factor for HCC development in patients with chronic hepatitis C (CHC). Approach and Results: In HCC cell lines, LG2m was expressed in alpha‐fetoprotein (AFP)‐negative, CD90‐positive cells characterized by highly metastatic natures. Using 14 cell lines and 258 HCC microarray data, we identified that LG2m gene signature was associated with Hoshida's S1/Boyault's G3 molecular subclasses with poor prognosis, which could not be recognized by AFP. Serum LG2m was assessed in 24 healthy donors, 133 chronic liver disease patients, and 142 HCC patients, and sensitivity and specificity of LG2m testing for HCC diagnosis were 62.9% and 70.5%, respectively (cutoff, 30 pg/mL). We evaluated the consequence of LG2m elevation in two independent HCC cohorts (n = 47 and n = 81), and LG2m‐high HCC showed poor prognosis with later development of distant organ metastasis (cutoff, 60 pg/mL). LG2m was slightly elevated in a subset of CHC patients, and Kaplan‐Meier analysis indicated a high incidence of HCC (n = 70). For validation, we enrolled 399 CHC patients with sustained virological response (SVR) as a multicenter, prospective study, and serum LG2m elevation correlated with a high incidence of HCC in the CHC patients with SVR ( P  < 0.0001). Conclusions: LG2m is a predictive biomarker for the development of metastatic HCC. Elevated serum LG2m is an HCC risk in CHC patients who have achieved SVR.